The Effect of Lavender Essential Oil Therapy on Reducing Anxiety Among Contraceptive Implant Acceptors at Tiley Health Center - Sulastri Safar; Retno Dewi Prisusanti (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Anxiety is a common psychological response experienced by contraceptive users, particularly among implant acceptors. Feelings of anxiety may arise due to hormonal changes, fear of side effects, and unpleasant experiences during contraceptive insertion. Aromatherapy using lavender essential oil has been shown to produce a calming effect through the activation of the limbic system and regulation of neurotransmitters, making it a potential method for reducing anxiety. This study aimed to determine the effect of lavender essential oil therapy on reducing anxiety among contraceptive implant acceptors at Tiley Health Center. A quasi-experimental design with a pretest-posttest control group approach was employed. A total of 30 respondents were randomly divided into treatment and control groups. The treatment group received inhalation of lavender essential oil for 10 minutes daily over three consecutive days, while the control group received no intervention. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS). The results indicated a significant reduction in anxiety scores in the treatment group before and after the intervention (p < 0.001), while the control group showed no meaningful difference (p > 0.05). These findings demonstrate that lavender essential oil aromatherapy is effective in reducing anxiety among implant contraceptive acceptors. This non-pharmacological therapy can be recommended as an easy, affordable, and safe complementary intervention in midwifery care services.